1994
DOI: 10.1259/0007-1285-67-797-478
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of radiation dose in examination of the abdomen using different radiological imaging techniques

Abstract: Typical radiation doses for abdominal examinations were determined for field sizes and entrance doses commonly selected on image intensifier based digital radiographic systems. In addition, measurements were also performed using conventional film-screen methods, a 100 mm camera combination and a phosphor storage computed radiography system. Both antero-posterior and postero-anterior projections were assessed. An anthropomorphic phantom loaded with lithium fluoride thermoluminescent dosimeters was used to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…This finding is in general agreement with previous workers where PA projections significantly reduced the dose level for abdominal examinations [10,11]. It must be acknowledged, however, that in previous studies effective dose was calculated, but this was not possible here due to the non-availability of conversion coefficients for the PA lumbar spine.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is in general agreement with previous workers where PA projections significantly reduced the dose level for abdominal examinations [10,11]. It must be acknowledged, however, that in previous studies effective dose was calculated, but this was not possible here due to the non-availability of conversion coefficients for the PA lumbar spine.…”
Section: Discussionsupporting
confidence: 92%
“…The dosemeter was placed in the midline, midway between the anterior and posterior surface representing a position occupied by the small intestine. The 38.9 % dose reduction recorded, coupled with the fact that the small bowel (along with numerous other radiosensitive organs [10]) is closer to the anterior than posterior surface, suggests significant advantages for this highly radiosensitive organ (and others) when the subject is positioned for a PA instead of an AP projection. The internal dose reduction, as well as the docu- Visually sharp reproduction of the intervertebral joints 3…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marshall 24 found that bAP projections give rise to higher effective doses than to PA projections because the majority of irradiated radiosensitive organs within the abdomen, such as the small intestine and others, lie closer to the entrance surface for the AP views in comparison to the PA views.Q In addition, the dense paraspinal musculature of the back will attenuate radiation better than would the subcutaneous fat of the anterior trunk, unless the fat is very thick.…”
Section: Radiation Dosementioning
confidence: 99%